MEDIA PROMOSI KESEHATAN SCRAPBOOK TENTANG GIZI SEIMBANG BAGI SISWA KELAS 4 (Politeknik Kesehatan Kemenkes Bandung, 2021)
Indonesia have multiple nutritional problems namely malnutrition and over nutrition (Rahmawati & Marfuah, 2016). Nutritional problems neet to be addressed because good nutrition will produce quality human resources namely health, smart, tought physique and productive. Education is the first pillar aimed at promoting healty living. In carriying out these health promotion effort is needed media (Notoatmodjo, 2010). This study aims to development a scrapbook health promotion media that can be used in balanced nutrition education. The research design used in this study is exploratory sequential mixed method design. At the qualitative stage, the researche explored the of the scrapbook media model, then at the quantitative stage the scrapbook health promotion media have a validated by validators theory expert and validators media expert and tested 13 person at 4 class student at SDN Cisoga 1. The result of qualitative research all respondents not undertstand the meaning of balanced nutrition. Scrapbook media that are interesting to lokk are those that have large images size, have a little writing and have attractive massage. Theme of scrapbook that like student about stories and animated or cartoon. The result of quantitative recearch the studi obtained a theory expert as much 86,6% in “very decent category”, a media expert as much 100% in “very decent category” and a tested media as much 98,9% “very decent category”. Expected scrapbook media that been tasted can be used as a learning media at SDN Cisoga 1 District Bandung.